Digesting development why Philippine industrialization hardly took off - Palma, Alexander Michael G. (Quezon City Tri-College, University of the Philippines Diliman, 2016)
"Institutions played a major role in the introduction of policy instruments that reflect the industrialization strategies adopted in specific post-independence era. Immediately after the Philippines gained independence, industrialization figured out in a certain pronouncements of the government that were criticized by nationalists because these pronouncements redound to a continued dependence on the U.S. economy. Foreign influences reflected prominently in hallmark trade and investment agreements, as well as in development assistance and forms of economic aid. These influences also mirrored the pattern of development of institutions which persisted for several years after independence. The paper attempts to examine how these influences resulted to the progression of industrial structure from its early origins to present from. These influences are mirrored in the ideas, language, and measured in monetary terms. The hypothesis of this paper is to provide validity to the assertion that mechanisms necessary to have initialized industrialization remain to be lacking in institutions of post-independence period. The paper is an attempt to provide the measureable parameters that will support this assertion and greater reforms in many aspects of governance."--Author
"The democratization process leading to the passing of the 1987 Constitution provided that, "the State shall promote industrialization and full employment based on sound agricultural development, and agrarian reform, through industries that make full use of human and natural resources, which are competitive in both domestic and foreign markets". It has been nearly three decades since such provision in the 1987 Constitution was articulated, but there remains up until now a lack of coherent, sound, and more defined industrial policy to speak of."--Author.
Thesis
Keywords: Industrialization -- Philippines; Philippines -- Economic policy; Philippines -- Economic conditions